Multiscale modeling and simulation in science| - Engquist, Björn (Springer, 2017)
Contains lecture notes of development in multiscale modeling, computations and applications. This book covers fundamental mathematical theory, numerical algorithms as well as practical computational advice for analysing single and multiphysics models containing a variety of scales in time and space. It treats complex fluids and porous media flow.